Pengelolaan Citra Cicalengka Dreamland Melalui Wisata Islam: Strategi Branding dan Pendekatan Dakwah dalam Industri Pariwisata - Nurizal Maulana, Mochamad; Darsono, Dono; Rahmi Astuti, Dyah (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
This study aims to find out how to define public relations problems planning, actuating, and evaluating the management of the Cicalengka Dreamland cira through Islamic tourism. The author uses the concept of four step public relations from Cutlip, Center and Broom. This concept was chosen because it is in accordance with the aspects that need to be considered in managing the image through the tourism concept. The paradigm used in this research is constructivist with a qualitative approach, and uses a qualitative descriptive method and data analysis from Miles and Huberman. Data collection techniques through observation, interviews, and documentation. The results of this study indicate that managing the image of Cicalengkka Dreamland through Islamic tourism is in accordance with the four step public relations stages which are divided into: 10. Defining public relations problems in managing image through the concept of Islamic tourism through observation and discussion with several religious leaders, 2). Image management planning through Islamic tourism is carried out with the stages of SWOT analysis, 3) actuating image management is carried out by providing the best facilities, optimizing services, outreach through Instagra, and collaboration with external parties, 4). Evaluating image management through Islamic tourism is carried out in short-term evaluations and long-term evaluations.